Penyuluhan Terpadu Pencegahan Kegawatan Penyakit Tidak Menular. Hipertensi dan Diabetes Mellitus di Kelurahan Mijen - Ainnur Rahmanti; Novita Wulan S; Anisa Mutiara Hanani; Auliya Rahma Putri; Ni Kadek Krisna Dwi Patrisia; Dana Faricha; Mutiara Andryani (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The Healthy Living Community Movement (GERMAS) is a program launched by the Ministry of Health to reduce the main risk of infectious and non-communicable diseases (NCDs), especially through nutritional interventions in the first 1000 days of life, improving balanced nutritional consumption patterns for the whole family, increasing regular and measurable physical activity. , improve healthy lifestyles, improve a healthy environment and reduce cigarette and alcohol consumption. Interview data showed that the majority of people, 48%, rarely had their health checked as early as possible, residents would go to the nearest health center if signs and symptoms of illness began to appear. Integrated counseling on prevention of emergency non-communicable diseases, Hypertension and Diabetes Mellitus, is carried out in one day, residents are gathered in the Mijen Village hall. The activity begins with simultaneous fitness exercises, then continues with a health check. The health checks carried out include anthropometric measurements in the form of height, weight, abdominal circumference, blood pressure measurements and random blood sugar measurements. Of the 50 residents who took part in the implementation of integrated counseling on the prevention of non-communicable disease emergencies. Hypertension and Diabetes Mellitus, as many as 24% of residents (12 people) just found out that they suffer from pre-diabetes mellitus, 16% (8 people) already know that they suffer from hypertension and diabetes mellitus, as many as 6% (3 people) have a stomach circumference of more than 100 cm, 54% (27 people) were in good health. Residents were quite enthusiastic about the activities carried out. The data obtained in the integrated counseling activity for preventing emergency non-communicable diseases, hypertension and diabetes mellitus, was submitted to the Mijen Community Health Center as a recap of data on the health status of the target area. The data obtained will be followed up by motivating residents to have their health checked at the Mijen Health Center.